2021
DOI: 10.1101/2021.03.08.434490
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Differential condensation of sister chromatids coordinates with Cdc6 to ensure distinct cell cycle progression inDrosophilamale germline stem cell lineage

Abstract: Stem cells undergo asymmetric division to produce both a self-renewing stem cell and a differentiating daughter cell. During Drosophila male germline stem cell (GSC) asymmetric division, preexisting old histones H3 and H4 are enriched in the self-renewed stem daughter cell, whereas the newly synthesized H3 and H4 are enriched in the differentiating daughter cell. However, the biological consequences in the two daughter cells resulting from asymmetric histone inheritance remained to be elucidated. In this work,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 101 publications
(121 reference statements)
0
1
0
Order By: Relevance
“…Conversely, the methylation of histone H3 at K9, K20, K27 and K36 have been suggested for their roles in initiating cellular differentiation [ 60 ]. Studies in Drosophila male GSCs have further revealed the potential roles of the differential phosphorylation of H3T3 and H3S10 during early mitosis, which are critical for stem cell maintenance [ 14 , 61 ]. Together, these findings suggest that the histone PTMs could indicate and regulate the differentiation status of stem cells.…”
Section: Establishment Of Asymmetric Epigenomementioning
confidence: 99%
“…Conversely, the methylation of histone H3 at K9, K20, K27 and K36 have been suggested for their roles in initiating cellular differentiation [ 60 ]. Studies in Drosophila male GSCs have further revealed the potential roles of the differential phosphorylation of H3T3 and H3S10 during early mitosis, which are critical for stem cell maintenance [ 14 , 61 ]. Together, these findings suggest that the histone PTMs could indicate and regulate the differentiation status of stem cells.…”
Section: Establishment Of Asymmetric Epigenomementioning
confidence: 99%